1905
DOI: 10.1152/ajplegacy.1905.14.4.313
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Studies on the Physiology of the Molluscs—second Paper

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1931
1931
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…There are particular advantages if the number of functions are few, since the elimination of the isotope will be affected by a minimum of environmental variables. The presence of large quantities of zinc in the digestive gland of gastropod mollusks was first reported by Mendel and Bradley ( 1905) . They suggested that the element served as reserve material for the formation of a respiratory pigment, "hemosycotypin."…”
Section: Discussionmentioning
confidence: 97%
“…There are particular advantages if the number of functions are few, since the elimination of the isotope will be affected by a minimum of environmental variables. The presence of large quantities of zinc in the digestive gland of gastropod mollusks was first reported by Mendel and Bradley ( 1905) . They suggested that the element served as reserve material for the formation of a respiratory pigment, "hemosycotypin."…”
Section: Discussionmentioning
confidence: 97%
“…86 This dye was also used by Mendel and Bradley to visualize the distribution of metals in hepatic tissues of the sea snail Sycotypus canaliculatus . 87 This study also employed sodium nitroprusside in what was the first demonstration of labile Zn 2+ in these tissues. Although this technique suffered from low sensitivity and therefore attracted little attention at the time, the reaction was later shown to be specific for Zn 2+ detection.…”
Section: A Brief History Of Visualizing Cellular Metal Ion Distributimentioning
confidence: 99%
“…The dye was later applied by Mendel et al for exploring the distribution of inorganic constituents in the liver of sycotypus canalicalatus 26. Haematoxylin is a natural product isolated from the logwood tree.…”
Section: Histochemical Techniquesmentioning
confidence: 99%
“…In 1905, Mendel and Bradley demonstrated for the first time the presence of labile zinc in hepatopancreatic tissues of sycotypus canalicalatus using sodium nitroprusside followed by alkaline sulfide development 26. Due to its low sensitivity, the protocol did not receive much attention at the time, despite the fact that the reaction was later demonstrated to be specific 47.…”
Section: Histochemical Techniquesmentioning
confidence: 99%